Comparative Analysis of a State University's Physical Plant and Facilities: Internal vs External Evaluations - Gomez, Abigail C.; De Grano, Ruby-Lyn T.; Valdez, Luningning A.; Gomez, Anabella C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In the landscape of higher education in the Philippines, institutions are subject to rigorous evaluations by accrediting bodies to ensure quality and adherence to standards. This study delves into the assessment of the physical plant and facilities of a state university, utilizing evaluations from both the university’s Internal Assessment Board (IAB) and the Accrediting Agency of Chartered Colleges and Universities in the Philippines (AACCUP) considered in this study as External Accrediting Body (EAB). Through a quantitative, comparative, and descriptive research design, document analysis was conducted on the ratings provided by the IAB and EAB across various parameters. The research instrument utilized was the AACCUP Accrediting Instrument, focusing on areas such as campus infrastructure, buildings, classrooms, and other essential facilities. Data were collected from the Institutional Development Office, encompassing two visits or evaluations across six academic programs. Statistical analysis such as mean, Mann-Whitney U Test, and one- way analysis of variance (ANOVA) were employed to identify differences between the ratings of the IAB and EAB. Remarkably, no significant differences were found in the evaluation of campus infrastructure, offices, staff, and function rooms, assembly and athletic facilities, medical and dental clinic, and food services unit/canteen. To wit, there is no significant difference between the two separate visits of the IAB [F(8,9) = .963, p = .516, not significant], no significant difference between the two separate visits of the EAB [F(8,9) = .238, p = .972, not significant], and no significant difference between the evaluation of the IAB and the EAB [Z= -1.549, p= .121, not significant]. The research findings highlight the importance of continuous improvement and transparency in assessing and enhancing education quality and facilities.